Human Adenovirus 11 in 2 Renal Transplant Recipients: Suspected Donor-Derived Infection. (25th February 2021) - Sherman, Amy C; Lu, Xiaoyan; Schneider, Eileen; Langston, Amelia; Ellis, Carla L; Pastan, Stephen; Bhatnagar, Julu; Reagan-Steiner, Sarah; Annambhotla, Pallavi; Lindstrom, Stephen; Mehta, Aneesh; Pouch, Stephanie M; et al.
Abstract: Background: Human adenovirus (HAdV) infections can lead to high mortality in solid organ transplant (SOT) recipients, with rare reports of donor-derived infection. Methods: Two renal transplant recipients with HAdV-11 infection who received kidneys from the same donor are described. Whole-genome sequencing (WGS) was performed. Results: WGS showed 100% nucleotide sequence identity for the 2 HAdV-11 isolates. The patients presented with distinct clinical syndromes, and both were treated with brincidofovir. Conclusions: Donor-derived HAdV infection is presumed to be low; however, disseminated HAdV in SOT recipients can be severe, and clinicians should be aware of the clinical course and treatment options.